2005
DOI: 10.1111/j.1365-4632.2004.02332.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of frequency, transmission, and genitourinary complications of enterobiasis (pinworms)

Abstract: Although transmission is often attributed to the ingestion of infective eggs by nail biting and inadequate hand washing, inhalation and ingestion of airborne eggs also occur. The female Enterobius vermicularis migrates nightly to the perianal area to deposit her eggs, but some worms find their way into adjacent orifices, most commonly the female genitourinary tract, producing an array of symptoms. More consideration of this entity is justified in patients presenting with genitourinary complaints not responding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
97
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 18 publications
(21 reference statements)
0
97
1
1
Order By: Relevance
“…Generally, the worms enter the vulva and vagina, where they remain for several days, and cause inflammation [12] [13]. Pinworms very rarely penetrate into the submucosa, but when they do, the results are often fatal [9]. Therefore, appropriate treatment and prevention are highly recommended.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the worms enter the vulva and vagina, where they remain for several days, and cause inflammation [12] [13]. Pinworms very rarely penetrate into the submucosa, but when they do, the results are often fatal [9]. Therefore, appropriate treatment and prevention are highly recommended.…”
Section: Introductionmentioning
confidence: 99%
“…Because children are often exposed to environments that are overcrowded, have inadequate sanitation, and engage in group activities more often than adults, this infection is more common in children [9] [10]. Currently, a number of young children are cared for at kindergartens or nurseries before they enter primary schools.…”
Section: Introductionmentioning
confidence: 99%
“…While Gutierres (Gutiérrez 2000) maintains that there exists a consensus that pinworms do not produce the inflammatory reaction. Cook (1994) stated that it is controversial whether pinworms are causatively related to acute appendicitis, and (Burkhart and Burkhart 2005) reported that pinworm infection causes symptoms of appendicitis to surface.…”
Section: Introductionmentioning
confidence: 99%
“…1 Moreover, ectopic infections of lung, liver and kidneys can occur. 6,7 In rare instances, female pinworms can enter the female genital tract to lay eggs leading to vulvovaginitis. In addition, pinworm infections adversely affect on the utilization of vitamin B12 and leading to lowered child's intelligence.…”
Section: Introductionmentioning
confidence: 99%